2022
DOI: 10.1007/s00190-022-01623-y
|View full text |Cite
|
Sign up to set email alerts
|

A sequential calibration approach based on the ensemble Kalman filter (C-EnKF) for forecasting total electron content (TEC)

Abstract: Ionospheric models are applied for computing the Total Electron Content (TEC) in ionosphere to reduce its effects on the Global Navigation Satellite System (GNSS)-based Standard Point Positioning (SPP) applications. However, the accuracy of these models is limited due to the simplified model structures and their dependency on the calibration period. In this study, we present a sequential Calibration approach based on the Ensemble Kalman Filter (C-EnKF) to improve TEC estimations. Its advantage, over the freque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 90 publications
(88 reference statements)
0
5
0
Order By: Relevance
“…Moreover, the study of Prietrella et al ( 2016) used the RMSE metric to compare the performance of different ionospheric models in this same eclipse. Additionally, both the RMSE and NRMSE metrics are commonly used to evaluate ionospheric model studies (e.g., Araujo-Pradere & Fuller-Rowell, 2002;Matsuo & Araujo-Pradere, 2011;Pignalberi et al, 2021;Kosary et al, 2022).…”
Section: Model-measurement Comparison Methodsmentioning
confidence: 99%
“…Moreover, the study of Prietrella et al ( 2016) used the RMSE metric to compare the performance of different ionospheric models in this same eclipse. Additionally, both the RMSE and NRMSE metrics are commonly used to evaluate ionospheric model studies (e.g., Araujo-Pradere & Fuller-Rowell, 2002;Matsuo & Araujo-Pradere, 2011;Pignalberi et al, 2021;Kosary et al, 2022).…”
Section: Model-measurement Comparison Methodsmentioning
confidence: 99%
“…Also, the advantage of this DA implementation for the near-real time orbit prediction and point positioning applications can be further explored. To improve the forecasting ability, it will be helpful to conduct further research on the calibration of external forcing (Forootan et al, 2020(Forootan et al, , 2022Kosary et al, 2022) using multi-sensor measurements.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the now-casting and forecasting capabilities of current empirical and physicsbased models are limited (i.e., one can find periods with over and underestimations) due to the lack of information about external drivers, simplified model structures, and the sensitivity to the calibration period (Forootan et al, 2020(Forootan et al, , 2022Kosary et al, 2022;Miyoshi et al, 2011;Palmroth et al, 2021;Vielberg et al, 2018). Thus, further enhancements, by taking advantage of the thermosphere-ionosphere observations, can improve characterizing and predicting thermosphere-ionosphere variability as accurately and efficiently as possible.…”
Section: Introductionmentioning
confidence: 99%
“…where 𝑑 , 𝑑 , and 𝑑 are the three components of the displacement vector 𝑑 in the north, east, and up directions, respectively. 𝜃 is the incidence angle and 𝛼 is the In order to consider the absolute difference between the observation and model in Figure 10, we used the average of absolute percentage deviation (AAPD) [70] as follows:…”
Section: Inferring Elastic Rebound From Gpsmentioning
confidence: 99%